2020
DOI: 10.5539/elt.v13n4p140
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Matters in Workplace: The Impact of Formal Mentoring Program on EFL Instructors’ Performance at ELI, King Abdulaziz University, Saudi Arabia

Abstract: An unprecedented acceleration in globalization, cross-culture integration and intensified innovation are a few elements that have triggered the need for availability of mentoring as the professional identity of any institution of higher learning. It has got the status of a foundation stone of mutual accomplishments between universities in the provision of teacher development. Therefore, this research study was carried out to evaluate the experiences of faculty members who participated in a formal mentoring pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…A study conducted by Khojah A et al at King Abdulaziz University in Jeddah revealed that 93% of the mentees opined that the mentor program is useful for the mentees personal and professional development and also stated that mentors are the back bone of any successful mentoring program [23]. The higher percentage can be attributed in that the study conducted at English Language Institute (ELI) at King Abdulaziz University, year of starting mentorship program, level of mentors training in mentorship program and there could be some sort of differences between the medical post graduate students versus undergraduate students and their faculty mentors.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Khojah A et al at King Abdulaziz University in Jeddah revealed that 93% of the mentees opined that the mentor program is useful for the mentees personal and professional development and also stated that mentors are the back bone of any successful mentoring program [23]. The higher percentage can be attributed in that the study conducted at English Language Institute (ELI) at King Abdulaziz University, year of starting mentorship program, level of mentors training in mentorship program and there could be some sort of differences between the medical post graduate students versus undergraduate students and their faculty mentors.…”
Section: Discussionmentioning
confidence: 99%
“…For mentor teachers, mentoring ELT student teachers during teaching practicum is beneficial in continuing their professional development and identity (Holland, 2018;Shanks et al, 2020). Khojah and Asif (2020) highlight the importance of mentoring for mentor teachers to focus on concrete demonstration and deconstruction of their teaching methods and practices.…”
Section: Mentoring In Eltmentioning
confidence: 99%
“…A third recommendation would be implementing a vigorous mentoring program for executives in leadership and including those desiring elevation to leadership roles within the organization. As outlined by Khojah and Asif (2020) mentoring is an essential and effective structure of supporting professional advancement. Mentoring is key in supporting the professional advancement of executives and increasing the efficiency of these employees.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%